DURIAN SEEDLING AGRIBUSINESS TO ACCELERATE THE SEED AVAILABILITY - Gede Mekse Korri Arisena; I Gusti Alit Gunadi; Anak Agung Keswari Krisnandika; Dwi Putra Darmawan; Nyoman Tri Lukpitasari Korri (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
The promising economic value of durian commodity is influenced by the superior characteristics possessed by each variety, especially its shape, thorn structure, taste, and thickness of the flesh. Durian agribusiness growth and expansion demands the constant availability of superior seeds. Missteps in utilizing durian seedlings will result in massive losses in time and energy put into the cultivation process, as it only could be seen after the plants bear fruit. Thus, the final objective of the study was to construct the durian seedling agribusiness model. To build a sufficient model, we initially investigated three major themes: 1) the grafting study on the four-week-old rootstock, 2) the grafting study on the two-month-old rootstock, and 3) the grafting study on the four-month-old rootstock. The eight-month study was conducted in an Experimental Garden owned by the School of Agriculture, Udayana University. Analysis of variance (ANOVA) applied to analyze the first, second, and third study aims. Depending on the analysis of the first, second, and third aims, the final objective was addressed using descriptive-qualitative analysis. Findings revealed that grafting on four-week-old rootstock was feasible. Additionally, findings reported that entres from the durian seedling did not provide optimal grafting results. Seeds from local durian varieties (consumable durian seeds) were sufficient for rootstock material. Findings suggested the utilization of local durian for the rootstock material due to their high viability in different vegetation types and tolerance to environmental stress. Entres from productive mother tree is highly advisable for grafting.